Comparing the Effect of Silk Fibroin-Based Scaffolds on Differentiation of Rabbit Chondrocytes - Mitra Naeimi; Mohammadhossein Fathi; Mohammad Rafienia; Shahin Bonakdar (مجله دانشکده پزشکی اصفهان, 2014)
Background: Osteoarthritis is a degenerative disease caused by damage or trauma to articular cartilage, leading to pain, brittleness, limitation of joint motions and swelling of the tissue. Cartilage damage is common in older people and also athletes. Chondrocytes dedifferentiate in monolayer culture. Tissue engineering involves the use of scaffold to maintain the differentiation of the cells. In this study, maintaining chondrogenic differentiation of the chondrocytes within the pure silk fibroin (SF) and silk fibroin- chondroitin sulfate- alginate (SF-CHS-SA) was compared.